Committee of Observation, New York, N.Y., meeting notices - Committee of Observation (New York, N.Y.)
Printed notices (1775 February 6 and April 10) for meetings of the Committee of Observation, New York, N.Y., held at the city's Merchant's Exchange. On the back of each notice are meeting notes reflecting the responsibilities and internal tensions of the committee. The notes written by an unidentified participant mention the committee's support for the decision of the Continental Congress to boycott British goods. Individuals mentioned include H. Berryen (possibly John Berrien), John Broome, Joseph Bull, James Duane, and Isaac Low. Notices are printed on partial sheets approximately three inches by seven and a half inches.
The Committee of Observation, also known as the Committee of Sixty, was similar to other committees formed in the colonies in the aftermath of what Americans referred to as the Coercive Acts or Intolerable Acts that were imposed by Great Britain in 1774 after the Boston Tea Party. The New York committee formed on May 16, 1774, and represented a coalition of interests including members of the Sons of Liberty, representatives of the city's craftsmen, small and large merchants, radicals, and moderates. As the Committee grew, the name changed from the Committee of Fifty-one to the Committee of Sixty, and later the Committee of One Hundred.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Berrien, John, -- 1735-1815.; Broome, John, -- 1738-1810.; Bull, Joseph; Duane, James, -- 1733-1797.; Low, Isaac, -- 1735-1791.; Committee of Sixty (New York, N.Y.); United States. -- Continental Congress; Great Britain -- Commerce -- United States; New York (N.Y.) -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- Commerce -- Great Britain; United States -- History -- Revolution, 1775-1783 -- Committees of observation